Influence Pengaruh Berkumur Jus Wortel (Daucus Carota.L) Terhadap Penurunan Skor Plak pada Anak Umur 10 Tahun Madrasah Ibtidaiyah Sullamul Khairiyah Kota Banjarbaru - Maharani, Rizqya; Astu Rahman, Waljuni; Nuryati, Sri; Kisworo Utami, Naning (Poltekkes Kemenkes Banjarmasin, 2025)
Based on the 2018 Riskesdas, the problem of damaged, decayed and diseased teeth in South Kalimantan has a rate of 46.9%, missing teeth due to extraction or self-dropping amounted to 17.8%, loose teeth amounted to 8.7%, and teeth have been patched / filled at 7.0%. In the Banjarbaru City area, oral health problems amounted to 33.4%. This study aims to determine the effect of gargling carrot juice on reducing plaque scores in 10-year-old children of Madrasah Ibtidaiyah Sullamul Khairiyah Kota Banjarbaru. This type of research is experimental research, pseudo experimental research design with one group pretest posttest and sampling by total sampling with a total of 45 students. Analysis of statistical test data using Paired Sample T-Test. The results of the research plaque score before gargling carrot juice obtained 2.90 and after gargling carrot juice obtained 1.13. Based on the results of the Paired Sample T-Test Test, it is known that the value of ???? = 0.000 is smaller than α (0.05) or ???? < α, in other words Ho is rejected and Ha is accepted. The conclusion is that there is an effect of gargling carrot juice on reducing plaque scores in 10-year-old children of Madrasah Ibtidaiyah Sullamul Khairiyah Kota Banjarbaru. It is recommended for Madrasah Ibtidaiyah Sullamul Khairiyah students and teachers to be able to use carrot juice as an alternative mouthwash to reduce plaque on the teeth.